The Use of the CIPP Model in the Evaluation of Social Programes: The Case of the Project Educating for Liberty (SECAD/MEC) - Wagner Bandeira Andriola (Universidad Autónoma de Madrid, 2016)
The article relates the use of the CIPP model to evaluate the 2nd Cycle of the Project Educating for Freedom (SECAD/MEC), that was carried out in six Brazilian States, and considered the following four dimensions: the Context (macro, meso and micro), the Resources (human and material), the Processes and the Products . Thus, an ex post-facto study was design to obtain relevant data on the referred dimensions, based in the following audiences: managers and penitentiary agents; professors, imprisoned students, and state technicians involved in prison education. The results show that the social effectiveness of the educational activities is imprinted in the qualitative changes on the inmates, changes, which are verified by the diverse social protagonists close to the imprisoned students.